Penerimaan Pesan Podcast Psikologid Sebagai Media Pembelajaran Untuk Kesehatan Mental Bagi Mahasiswa - Fadhila Cahya Kawiswara; Indah Wenerda (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2022)
As time goes by, information technology is increasingly developing which makes it easier for humans to create new media including audio media. Year 2020 is the year of the 'New golden age of audio' in which podcast listeners have tripled. Apart from that, 2020 was also the year when the Covid-19 pandemic appeared in Indonesia and had an adverse effect on the students’ mental health. The podcast that will be discussed in this study is one of the podcasts that are already present on Spotify which discusses mental health, namely the Psikologid podcast. The purpose of this study is to find out how the acceptance of Psikologid podcast messages as a learning medium for mental health for students. This study used a type of qualitative research with a descriptive approach. The results of this study indicate that of the eight informants who have been selected, four informants belong to a dominant hegemonic position, three informants belong to a negotiating position, and one informant enters an oppositional position that rejects or is not in line with the message conveyed through the Psikologid podcast. With different backgrounds, the eight informants have different responses about the messages they received through the Psikologid podcast.